Mainstreaming Domestic and Gender-Based Violence into Sociology and the Criminology of Violence. (December 2014) - Walby, Sylvia; Towers, Jude; Francis, Brian
Sociological and criminological views of domestic and gender-based violence generally either dismiss it as not worthy of consideration, or focus on specific groups of offenders and victims (male youth gangs, partner violence victims). In this paper, we take a holistic approach to violence, extending the definition from that commonly in use to encompass domestic violence and sexual violence. We operationalize that definition by using data from the latest sweep of the Crime Survey for England and Wales. By so doing, we identify that violence is currently under-measured and ubiquitous; that it is gendered, and that other forms of violence (family violence, acquaintance violence against women) are equally of concern. We argue that violence studies are an important form of activity for sociologists.